International chamber of commerce (icc) code On advertising practices and sri lankan advertisements - Grace, H.H.; Dilogini, S. (University of Jaffna, 2017)
Advertising has a crucial role in today's competitive business environment. Advertising is a mode of communication between seller and the buyer. The current business trend involves the emergence of new business entities and new business practices in Sri Lanka. The business enterprises should follow the codes and rules in every business activities. If they do not follow the rules, the bad practices will increase constantly. We see the emergence of new marketing practices and policies that will affect the organizations in the years to come. Organizations need to create a business environment which increases the sales and enhances customer relationship. Communication is the most crucial thing which organizations need to cultivate to enhance the relationship with the customers. Though there are many forms of communication, advertisement is the most popular communication method. This method helps to communicate with the people in a cost effective way as well. There are different types of advertisement such as TV ads, newspaper ads, radio ads, cinema ads etc. There is a common international code on advertising which most of the countries follow during their ads. But there is no proper code or rules & regulations on advertising practices in Sri Lanka. Even though Sri Lankan marketers and Advertising agencies should follow ethical practices in their advertising policies and advertising designs. This study has identified some gaps in real advertising practices compare with ICC code on advertising practices which are useful for future marketers and advertising agencies. Researchers have used discourse analysis method to identify gaps in real practices and ICC code on advertising practices and present their findings. Through these findings, researchers wish to make awareness to the customers as well as the marketers on the advertising rules and regulations. Sri Lankan advertising authority must launch the codes of advertisements in Sri Lanka. Moreover, some Sri Lankan advertisements violate the ICC Code of advertisements. More attention should be paid to content and truthfulness of messages.
Keywords: Advertisement; Advertising Practices; ICC Code; Advertising agency; Awareness